Severity of premenstrual syndrome (PMS) and its related factors in students of Shahid Beheshti University of Medical Sciences - Ozgoli, G; Selselei, E; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and aim Premenstrual syndrome (PMS) is one or more symptoms from a great combination of physical, psychological and behavioral symptoms, occurring in 70%-90%of women at childbearing age. 95% of women suffer from mild symptoms of PMS while, in 3%-10%, the symptoms are severe and disabling. The aim of this study was identify the severity of PMS and its related factors in students of Shahid Beheshti University of Medical Sciences & Health Services,. Materials and methods In this descriptive study, of 980 students in the dormitories of the university, 85 with PMS were selected by purposive sampling method. Data collection tools included a demographic questionnaire and a diary form derived from criteria of Diagnostic and Statistical Manual IV (DSM-4). Validity and reliability of the tools were determined by content and test-retest (r=0.82) methods respectively. Data collection method was self report questionnaires. Findings Means of age and body mass index of the subjects were 22.20 and 22.59 respectively. 58.8%, 38.8% and 2.4% had mild, moderate and severe physical symptoms respectively. The corresponding figures for psychological symptoms were 30.7%, 66.1% and 3.2 respectively. Conclusion The severity of symptoms in more than two thirds of the subjects was moderate and mild. A significant relationship was found between the onset of symptoms as well as educational term of the students and syndrome severity. Keywords: Premenstrual syndrome (PMS), Student, Menstrual disorders. *Corresponding Author: Giti, Ozgoli. Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences & Health Services, Tehran, Iran E-mail: gozgoli@Yahoo.com